A passionate craftsman and his craft: reflections on Wynne Godley's work and legacy. Issue 1 (2nd January 2021) - Dos Santos, Claudio H.
Abstract: The text has three main goals. The first is to share some of the author's personal recollections on (briefly) working as Wynne Godley's research assistant. The second is to reflect on the origins of the term/brand "stock-flow consistent" (or SFC, for insiders), which is at once successful (given the number of people who seem to like using it) and controversial. The third and most important is to reflect on Wynne Godley's approach to macroeconomics—however, one wants to call it—and legacy.